STUDY OF SEDIMENTATION IN THE WATER OF PATIMBAN PORT DEVELOPMENT PLAN USING COMPUTATION MODELING - Mardi Wibowo (Jurnal Kelautan Nasional, 2018)
The developmentof the international port of Patimban in Subang is very urgent. The port is expected to support the Tanjung Priok port in Jakarta which is unable to meet the loading and unloading needs of business operators, especially in West Java. In port development planning one of the main problems of physical chemical aspects is sedimentation and erosion process. The purpose of this modeling is to know the sedimentation and erosion pattern around the location plan of port development. The result of modeling is expected to be the initial consideration in designing the Patimban Port. Modeling of sediment transport is done by using MIKE21 Sand Transport module software by entering geophysical data of field survey result such as bathymetry, sea level, river flow and characteristic of existing sediment. Modeling is done both in west season and east season for 1 year (October 2016-September 2017).Based on the results of this modeling is known that the existing conditions in parairan construction plan ponds occur sedimentation sedimentation of 12.74 cm / m th while when the port has been built a little erosion -0.34 cm / year. Whereas in the existing shipping lane plan there is sedimentation 14,41 cm / year and when the port has been built there is sedimentation of 6,06 cm / year.